Prospective Applicability of E-Health Services: An Overview of Advantages of Telemedicine and Telenursing: Aplicabilidad prospectiva de los servicios de salud en línea: una visión general de las ventajas de la telemedicina y la telenfermería - Nieto Chaupis, Huber (2017)
In this paper, we review the prospects of applicability of the expected services of E-Health in large cities, in order to assess the possible advantages and notable virtues which might be consistent with the ongoing intrinsic economic and social factors. We have paid attention to the mechanisms of the E-Health and how it can be crucial or also, be still premature to be implemented since it depends of logistic, budges, specialized professionals, and high level equipment. To illustrate all that, a scenario where E-Health target to improve the quality of life of diabetic patients, which are already starting with irreversible complication because the uncontrollable evolution of glucose and others diabetic indicators, is presented. From this review, one can find that there is notable featuring the implementation of E-Health services which can be implemented in large cities. However, restrictions of the applicability might degrade the quality of service of the E-Health service.